IMPROVEMENT PROSPECTS OF THE UKRAINIAN EDUCATIONAL SYSTEM IN THE CONTEXT OF THE HUMAN DEVELOPMENT CONCEPT - Loza, Tatiana (Educological discourse, 2020)
The results of a scientific search dedicated to the problem of educational services transformation and whole education system adaptation to the challenges of the modern labor market were discussed in the article. The relationship between the problems of the Ukrainian labor market, the outdated educational system and inefficient human potential using is established. The essential correlation between the priority directions of human development for Ukraine and the main directions of educational system reforming are determined. Based on the analysis of the Human Development Index in Ukraine and other statistical indicators, directions for development and realization of social and educational service are determined with the condition of attraction of non-governmental organizations. The necessity of introducing new practical approaches was developed and theoretically substantiated for: · Expanding the range of entities providing educational services based on public-private partnership; · Establishing the accordance between the number of university applicants and request for them in the labor market; · Increasing the value of education through establishing the relationship between its level and the well-being of the employee; · Creating conditions for the dynamic adjustment of the content of education, depending on the labor market trends. The necessity of introducing new practical approaches for more effective development of human potential by restoring the education value and providing productive employment has been developed and theoretically substantiated.